Mn–Cr systematics in primitive meteorites: Insights from mineral separation and partial dissolution. (1st May 2015) - Göpel, Christa; Birck, Jean-Louis; Galy, Albert; Barrat, Jean-Alix; Zanda, Brigitte
Abstract: Cr isotopic compositions have been measured on carbonaceous chondrites (CC): Tafassasset, Paris, Niger I, NWA 5958, NWA 8157 and Jbilet Winselwan. In bulk samples, the 54 Cr/ 52 Cr ratios (expressed as ε 54 Cr) range from 0.93 to 1.58 ε units. These values are in agreement with values characteristic for distinct petrologic types. Despite this 54 Cr heterogeneity, the variability in the 53 Cr/ 52 Cr ratios (expressed as ε 53 Cr) of 0.2 ε units and the Mn/Cr ratios is consistent with the previous finding of an isochron in the Mn–Cr evolution diagram. The Mn/Cr ratio in CC corresponds to variable abundances of high-T condensate formed and separated at the beginning of the solar system, thus the canonical 53 Mn/ 55 Mn ratio can be defined. Based on a consistent chronology for U–Pb and Mn–Cr between the earliest objects formed in the solar nebula and the D'Orbigny angrite we define a canonical 53 Mn/ 55 Mn ratio and ε 53 Cri of 6.8 × 10 −6 and −0.177, respectively. The internal Mn/Cr systematics in Tafassasset and Paris were studied by two approaches: leaching technique and mineral separation. Despite variable ε 54 Cr values (up to >30 ε) linear co-variations were found between ε 53 Cr and Mn/Cr ratio. The mineral separates as well as the leachates of Tafassasset fall on a common isochron indicating that (1) cooling of the Tafassasset's parent body occurred at 4563.5 ± 0.25 Ma, and that (2) 54 Cr is decoupled from the other isotopes even though temperatures >900 °C have been reached during metamorphism. In the case of Paris, the leachates form an alignment with a 53 Mn/ 55 Mn ratio higher than the canonical value. This alignment is not an isochron but rather a mixing line. Based on leachates from various CM and CI, we propose the occurrence of three distinct Cr reservoirs in meteoritic material: PURE54, HIGH53 and LOW53 characterized by a ε 53 Cr and ε 54 Cr of 0 and 25, 000, −2.17 and 8, and 0.5 and −151, respectively. PURE54 has already been described and is carried by highly refractory nano-spinel; HIGH53 is Mn-rich and most probably carried by sulfides in the matrix, whereas LOW53 is characterized by low Mn/Cr ratios and it is sensitive to metamorphism. This component could correspond to mineral phases such as refractory oxides and carbide. Variable mixing proportions of HIGH53 and LOW53 would explain the larger-than-expected uncertainty (MSWD of 5.5) on the CC bulk regression line. A Monte Carlo simulation allows us to evaluate the impact of the dispersion of the initial Cr isotopic ratios (as a function of variable HIGH53). The co-variation of the Mn/Cr ratio and the ε 53 Cr defined by the mineral separates from Paris corresponds to an age of 4566.44 +0.66 /−0.75 Ma, while their ε 54 Cr still differ by at least 0.42 ε. This age is likely to date the segregation of forsteritic olivines (most probably from type I chondrules) from fayalitic olivines (from type II chondrules) and, given the sampling procedure by handpicking of hundreds of grains, corresponds to the average age of chondrule formation.